SIM PAUD Application Training in Improving Teacher IT Skills at PPT Permata Hati Bendul Merisi Wonocolo District - Firda Rizqy Amalia; Suryanto Suryanto (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
As science and technology advance along with the growth of industry 4.0, teachers are expected to be able to adjust their skills to current demands. In a specific subject, skills or knowledge that are defined by professionalism become the most essential item as the field's flagship. Competence is required in all disciplines, including teaching methods. The role of teachers in educating and attempts to maximize all brain cells in children are inextricably linked to the success of Early Childhood Education. Given the golden age in humans is 0-6 years. Thus, this study aims to identify the readiness of teacher competencies to educate students in the face of an ever-increasing flow of technology. The objective of this study was to discuss the IT training provided at PPT Permata Hati to help teachers enhance their IT skills in creating online lesson plans. A qualitative method was employed in this study, utilizing a case study approach. Data was gathered through interviews, documentation, and activity pictures. The results of this study revealed the progression of the educational process at PPT Permata Hati in Bendul Merisi Village, Wonocolo District, from the creation of learning activity plans by teachers using the SIM PAUD application to online performance reporting through the Surabaya City Department of Education's website. The training outlined the principal's training, which included everything from an introduction to how to use the program. A presentation and on-the-job training methodology were employed as the training model. The originality or value of this study is that it discusses the training given to early childhood teachers on how to use the Surabaya City Department of Education's information technology